HADITH AL-MACHADI (1689-1770) AND HIS MANUSCRIPT COLLECTION - Abdulmazidov, Ramazan Sultanovic; Anikeeva, Tat'ana Aleksandrovna; Sehmagomedov, Magomed Gadzievic (History, Archeology and Ethnography of the Caucasus, 2024)
This paper presents an overview of the private manuscript collection of Hadis al-Machadi (1689–1770), examined and partially digitized during the archaeographic expedition funded by the RSF grant No. 22-18-00295 “Electronic library of Arabic-language manuscripts from archival, library, museum and private collections of Russia” in the summer of 2023. The collection, notable for its thematic and chronological diversity, spans several centuries and encompasses materials in Arabic from various sources, including manuscripts directly associated with Hadis al-Machadi, those of his descendants, and other scholars from the village of Machada in the Shamilsky district of the Republic of Dagestan. Notably, the library includes works by Sufi authors and a significant corpus of letters, documents, legal records, and court decisions, offering fertile ground for further scholarly exploration. Among the manuscripts are rare or unique pieces such as “Silsilat al-masnuʻat” by Ahmad Zirikhgerani and “Hashiya ʻala Charpardi”. Moreover, the inclusion of works from the 19th and 20th centuries, likely acquired through the Gidatlin Ulama, underscores a tradition of continuity of Arab-Muslim studies in the region.